Cyclic AMP signaling promotes regeneration of cochlear synapses after excitotoxic or noise trauma - Hemachandran, Sriram; Hu, Ning; Kane, Catherine J.; Green, Steven H. (Frontiers in Cellular Neuroscience, 2024)
Cochlear afferent synapses connecting inner hair cells to spiral ganglion neurons are susceptible to excitotoxic trauma on exposure to loud sound, resulting in a noise-induced cochlear synaptopathy (NICS). We mimicked this trauma in an in vitro model by applying a glutamate receptor agonist, kainic acid (KA) to organotypic cochlear . Regeneration of the lost synapses is very limited but, we show here, can be promoted by cAMP signaling in the in vitro model and in noise-exposed mice. Indeed, using the in vitro model, we show that the application of the cell membrane-permeable cAMP agonist 8-cpt-cAMP or the cAMP phosphodiesterase inhibitor rolipram promotes significant regeneration of synapses within twelve hours after their destruction by KA. This is independent of neurotrophin-3, which also promotes synapse regeneration. Two independent signaling effectors are activated by cAMP: the cAMP Exchange Protein Activated by cAMP and the cAMPdependent protein kinase. We show here that it is the latter that mediates synapse regeneration. Finally, we show that systemic delivery of rolipram from a subcutaneously implanted minipump in adult mice promotes synapse regeneration in vivo following NICS.Thus, systemic administration of rolipram or similar compounds may provide a minimally invasive therapeutic approach to reversing synaptopathy post-noise.